Advances in food and nutrition research. - Kinsella, John E., 1938- (Advances in food and nutrition research, 1993)
Advances in Food Research, the leading publication for comprehensive reviews on important topics in food science, has evolved into Advances in Food and Nutrition Research under the editorial direction ofJohn E. Kinsella. This expanded title recognizes the integral relationships between food science and nutrition and presents reviews of topics in nutrition as well as food science. This change also encourages nutritionists and food scientists to become more familiar with relevant advances in these interrelated areas.